Forma em fluxo: transformações na concepção estética do objeto no século XIX - Denis, Rafael Cardoso (1991)
The heightened concern with the decorative arts at the close of the 19th century is the prodcut of a cross between optical and tactile values which, in turn, derives from a loss of the primary tactile relationship between man and object, brought on by industrialization. This process is most evident in the relationship between painting and the decorative arts, which provides the historical data for the investigation at hand. Using Riegl, Berenson and Gombrich, an analysis is made of the ties between the Pre-Raphaelite and the Arts and Crafts movements, pointing out the link between painting and the decorative arts. A theoretical model is set up through the discussion of the concept of stylization, as encountered in the works of Ruskin, Owen Jones and Araujo Porto-Alegre. The model is tested through the study of the link between Symbolism and Art Nouveau, in France and in Brazil.